Internal Efforts of Improving Spirituality of Ministry Apartment of Religion, Medan City - Siregar, Impun; Muzakkir, Muzakkir; Nur, Anwarsyah (Budapest International Research and Critics University, 2019)
The aim of this research is to analyze the spirituality of the State Civil Apparatus at the Office of the Ministry of Religion in Medan, the researcher will link and relate the benchmarks of this research to the Indonesian Minister of Religion's program